O Programa de Aceleração do Crescimento (PAC) na Região Metropolitana de Maringá/PR - Jordão, Vitor Luis Colli (2012)
In January 2007 the Growth Acceleration Program was launched by the Federal Government (PAC), giving direction to the economical growth of the country, causing an increase in job offers and an overall improvement in living condition of the Brazilian population. According to the Government, the Program is composed of a set of measurements with the purpose of encouraging the private investments, increasing the public investments in energy infra-structure, urbanity plan in order to overcome the obstacles ( which are bureaucratic, management, norms, judicial and legislative obstacles) of the economical and social growth of the country. Since this Program has de objective of increasing the national economical growth, this research proposes the analysis of investments in Paraná State, with emphasis on the resources directed to the Metropolitan Regions, specifically Maringá Region. Such analysis is based on documents and information available from the government and studies developed by Metropolitan Observatory Network. Based on the hypothesis that the PAC Projects have the tendency to confirm the historical contradictions of the State actions upon the national space, corroborating with the tradition of a selective territorial development, concentrated and uneven, reinforced by the dominant political and economical interests once the distribution of resources through approval of projects has not been allotted evenly in the Metropolitan Regions of the State, and much less in the districts that comprise the Region.